The tourism spectacle of fire making at Coranderrk Aboriginal Station, Victoria, Australia – a case study. Issue 3 (3rd May 2020) - Clark, Ian D.; McMaster, Sarah; Roberts, Phillip; Cahir, Fred; Wright, Wendy
ABSTRACT: This paper explores the emergence of traditional Aboriginal fire making practices as a tourism spectacle at the Coranderrk Aboriginal Station near Healesville, Victoria, Australia, in the late nineteenth century. Coranderrk was an important site where domestic and international tourism intersected with efforts of the state to Europeanise and Christianise its Aboriginal residents. It highlights the agency of Aboriginal people in this emergence. Through a survey of the myriad uses of fire in Aboriginal society, it contrasts Aboriginal methods of making fire with European methods as a way of contextualising the tourist interest in fire making demonstrations. Fire making was the perfect foil for tourism – it easily incorporated aspects of performance – such as the build, the show, the closer, and the hat. The skill of fire making was a demonstration of 'Aboriginality', and its appropriation by tourism was a means by which a traditional craft was maintained and sustained.